In the Middle of Nowhere - Howe, Fanny (Book collections on Project MUSE., 1984)
In the middle of nowhere is a fictional story set in a New England town. It shows a glimpse into the meeting of the lives of four characters. Moods of landscape and weather reflect their states of mind, and incline them towards actions which represent the terminal points of character.